Analisis Pengaruh Social Distancing, Work from Home dan Aplikasi Video Call terhadap Produktivitas Organisasi: Studi Kasus pada Permukiman di DKI Jakarta - Dewi Puspaningtyas Faeni; Ratih Puspitaningtyas Faeni; Ravindra Safitra Hidayat; Retno Fuji Oktaviani; Rinny Meidiyustiani (Penerbit Goodwood, 2021)
Purpose: This research aimed to analyze the influence of Social Distancing, Work from Home and Video Call applications towards Organizational Productivity. Method: This type of research is a quantitative descriptive research. The analysis tool used in this study is SmartPLS 3.0. The population of this study is 9880 people. The samples studied were 130 people using the Simple Random Sampling method. The sampling technique refers to the Slovin formula. The results stated that the analysis of Social Distancing influence, Work From Home and Video Call application (0,052), (0,047) and (0,924). Results: Based on test of R Square, Productivity of the Organization as Endogenous variable affects 98.6% while the remaining 1.4% is influenced by other factors.